2016
DOI: 10.4062/biomolther.2016.076
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of GABA-A Receptor Subunit Alpha 3, Gabra3 and Lipoprotein Lipase, Lpl Are Associated with the Susceptibility to Acetaminophen-Induced Hepatotoxicity

Abstract: Drug-induced liver injury (DILI) is the serious and fatal drug-associated adverse effect, but its incidence is very low and individual variation in severity is substantial. Acetaminophen (APAP)-induced liver injury accounts for >50% of reported DILI cases but little is known for the cause of individual variations in the severity. Intrinsic genetic variation is considered a key element but the identity of the genes was not well-established. Here, pre-biopsy method and microarray technique was applied to uncover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Meanwhile, Dio3os was also highly expressed in artificial and in vitro decidualization. A microarray experiment reported that Gdap10 was highly expressed in acetaminopheninduced liver injury (Kim et al 2017). Hepatocyte chromosome polyploidization is an important response to liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Dio3os was also highly expressed in artificial and in vitro decidualization. A microarray experiment reported that Gdap10 was highly expressed in acetaminopheninduced liver injury (Kim et al 2017). Hepatocyte chromosome polyploidization is an important response to liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, APAP overdose is one of the leading causes of DILI globally accounting for >50% of cases (5). It has proven difficult to elucidate the specific pathogenesis of DILI due to the differing severity of symptoms between patients resulting from individual differences (6).…”
Section: Introductionmentioning
confidence: 99%
“…Liver histology in zebrafish: Zebrafish larvae were collected and fixed in 10% neutral buffered formalin at room temperature overnight and were then subjected to paraffin embedding and sectioning. Hematoxylin and eosin staining was performed to histologically examine hepatotoxicity as described previously ( Jeong et al ., 2017a ; Kim et al ., 2017 ).…”
Section: Methodsmentioning
confidence: 99%